The effect of body shaming on self-confidence - Rayha Warda Akhfani; Slamet Hamid (Asosiasi Asesmen Pendidikan (AAP), 2025)
Body shaming remains a prevalent issue among adolescents and has been shown to impact their psychological well-being, making it an urgent concern within the educational context. This study aims to analyze the effect of body shaming on self-confidence and to describe the implications for counseling guidance among high school students in Depok. The research employed a quantitative approach with a sample of 150 tenth-grade students. The normality test showed that the body shaming variable had a significance value of 0.051 (> 0.05) and the self-confidence variable had a value of 0.080 (> 0.05), indicating that both variables were normally distributed. The linearity test produced a significance value of 0.525 (> 0.05), confirming a linear relationship between the variables. Furthermore, the simple linear regression test yielded a significance value of 0.002 (< 0.05), demonstrating that body shaming has a significant effect on self-confidence. These findings indicate that higher levels of body shaming are associated with lower levels of self-confidence in students, highlighting the need for effective school counseling interventions to address and mitigate its impact.